Effect of Fenugreek Seed Extract on Osteoblasts, Osteoclasts, and Neocapillaries After Extraction in Hypoestrogenic Rats - Ester Handayani Lodra; Fitriana Fitriana; Athallah Nisrina Amanda; Ossana Bernicha Nugroho; Azza Cindikia (Faculty of Dentistry, Universitas Islam Sultan Agung, 2026)
Background: Hypoestrogen is characterized with lower level of estrogen hormone that affects wound healing following tooth extraction. In a hypoestrogenic condition, the post-extraction healing prosses is marked by the osteoblasts count, increased activation of osteoclasts, and suppressed the neocapillaries count. Fenugreek seeds with compounds such as diosgenin, quercetin, galactomannan, trigonellin and lupeol can potentially stimulate osteoblasts formation, suppress the number of osteoclasts cells, and increase the neocapillaries count. Purpose: To evaluate the influence of Fenugreek seed extract (FSE) on administration on osteoblasts, osteoclasts, and neocapillaries count in the post-extraction socket of hypoestrogenic rat teeth.Methods: True experimental study and the design that was used is Post Test Only Control Group Design. Female Wistar rats were used as experimental subjects and assigned to two untreated control groups and three treatment groups receiving fenugreek seed extract at doses of 100, 200, and 400 mg/kgBW. The right maxillae of rats euthanized on days 3, 7, and 30 were processed into histological sections, stained with hematoxylin–eosin (H&E), and examined under a microscope at 400× magnification across ten fields of view. Results: This study was analyzed using the Tukey post-hoc test demonstrated statistically significant differences in osteoblast numbers, osteoclast counts, and neocapillary density (p < 0.05).Conclusion: Fenugreek seed extract affects increasing the osteoblasts, decreasing the osteoclasts, and enhance neocapillary development following tooth extraction in hypoestrogenic White Wistar rats.